Critical Reading Strategies Employed by Good Critical Readers of Graduate Students in ELT, State University of Malang - Praptika Sefta Femilia (UMBanjarmasin, 2018)
The objective of the study was to find out how good critical readers employed their critical reading strategies and what model of reading shown by these strategies. Qualitative approach was applied in this study with case study as the research design. This study involved three good critical readers determined by the result of reading comprehension test given. The data were collected through retrospective think aloud and in depth interview. This study reveals that these three good critical readers employed nine critical reading strategies which consist of strategies for constructing the meaning of the text; they were previewing, questioning to understand and remember, monitoring comprehension, solving vocabulary problems and interpreting the text; and strategies for evaluating the arguments presented by the writers which consist of contextualizing, reflecting on challenges to belief and values, evaluating the writers’ arguments and; comparing and contrasting related reading. It was also found that the pattern of how these strategies utilized formed interactive model of reading. It is suggested to further researches to focus more on discussion about critical reading strategies which are related to reasoning evaluation.